Equity and trusts - Hudson, Alastair (Routledge-Cavendish, 2010)
Suitable for undergraduate courses on the law of trusts and equitable remedies, this book provides an account of the subject. It helps students to build and develop their own knowledge of equity and trusts. It features essays reflecting on the law. It outlines the broader political, social and economic context of the subject.